Rajburicoris, a new genus of Cardiastethini, and discussion of the systematic position of Dufouriellus (Hemiptera: Heteroptera: Anthocoridae) - Carpintero, Diego Leonardo (2008)
Rajburicoris stysi gen. nov. and sp. nov. from Thailand is described and the male and female genitalia are examined and illustrated. A review of the diagnostic characters of the tribe Cardiastethini Carayon, 1972, nom. restit., is given. The systematic position of the controversial genus Dufouriellus Kirkaldy, 1906, is discussed and the genus is transferred to Anthocorini; Dufouriellini Van Duzee, 1916, syn. nov., becomes a junior synonym of Anthocorini.